Ketika Regulasi Bertemu Kearifan Lokal: Tantangan dan Peluang Implementasi Peraturan Desa Penertiban Ternak - Melin Wula, Handrianus Vianey; Y. Gabriel Maniagasi (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to determine the implementation of the Village Regulation (Perdes) on livestock management in Humusu Wini Village, North Central Timor Regency, Indonesia. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation with selected informants, including village officials, BPD members, security forces, and livestock owners. The results indicate ongoing challenges in communication, institutional coordination, and socio-cultural acceptance. Inconsistent outreach limited community understanding, while weak coordination reduced the BPD's oversight function. Security forces tended to use a repressive approach, which fueled resistance. From an economic perspective, most households considered the cost of building cages unaffordable, and culturally, the custom of releasing livestock remained strong. The study concluded that successful policy implementation requires more than formal regulations; it requires ongoing communication, material support, a persuasive approach, and respect for local wisdom. Collaborative governance is key to ensuring community acceptance and sustainability of the policy. Keywords: Collaborative Governance, Community Participation, Livestock Control, Local Wisdom, Policy Implementation, Village Regulation.